Nieliniowa analiza płyt włóknokompozytowych - Kula, Krzysztof
The main goal of the work is the modelling and numerical simulation of fibre-composite plates in the nonlinear range due to large displacements and damage. Two finite element models are presented for prediction and description of the failure progression. The first (2-D) model is based upon the stress failure criteria and material modification in the material point with failure. The model leads to good results for the simulation of intralaminar failure but is not sufficient for the modelling of the complete state of failure.
Keywords: metoda elementów skończonych; mechanika uszkodzeń; płyta włóknokompozytowa